2010
DOI: 10.3748/wjg.v16.i9.1063
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing intercellular spaces in the rat esophageal epithelium

Abstract: Acute stress and aspirin can induce DIS of the esophageal epithelium in rats, and it is not correlated with acid reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Using electron microscopy, we confirmed the widening of the intercellular spaces of the esophageal epithelia in the SB, SS, and SG in the RE group in comparison with the control group, as previously reported (Farré et al, 2007;Miwa et al, 2009;Ito et al, 2010;Zhang et al, 2010). This result suggests that the esophageal epithelia in rat RE models were affected by acid reflux, which is consistent with previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…Using electron microscopy, we confirmed the widening of the intercellular spaces of the esophageal epithelia in the SB, SS, and SG in the RE group in comparison with the control group, as previously reported (Farré et al, 2007;Miwa et al, 2009;Ito et al, 2010;Zhang et al, 2010). This result suggests that the esophageal epithelia in rat RE models were affected by acid reflux, which is consistent with previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…Animal studies regarding reflux esophagitis induced by esophagoduodenostomy reveal that the earliest sign of esophageal inflammation is an infiltration of the submucosa by white cells that is cytokine-mediated and precedes the development of surface lesions by weeks [7]. This immune system response is supported by transmission electron microscopy, which showed no evidence of inflammation in the esophageal mucosa in response to acute stress, hydrochloric acid, ethanol, aspirin or prednisolone [8].…”
supporting
confidence: 52%
“…It has been shown that aspirin makes the esophageal mucosa more sensitive to the injurious action of acid and pepsin (44). In another study, intragastric administration of aspirin induced dilated intercellular spaces in the rat esophageal epithelium (45). In addition, some studies have observed that treatment with high doses of ASA provokes both significantly increased production of reactive oxygen species (ROS) (46) and inhibition of ROS scavenger activity (47).…”
Section: Discussionmentioning
confidence: 99%